Hypertensive disorders of pregnancy and subsequent risk of solid cancer—A nationwide cohort study. Issue 1 (25th March 2016) - Behrens, Ida; Basit, Saima; Jensen, Allan; Lykke, Jacob Alexander; Nielsen, Lars Peter; Wohlfahrt, Jan; Kjær, Susanne K.; Melbye, Mads; Boyd, Heather Allison
Abstract : Women with hypertensive disorders of pregnancy (HDP) have higher levels of antiangiogenic growth factors during pregnancy than women with normotensive pregnancies. Since angiogenesis is necessary for solid cancer growth and spread, we hypothesized that women with a history of HDP might have a reduced risk of solid cancers (cancers other than lymphomas, hematologic cancers and nonmelanoma skin cancers) later in life. In a register‐based cohort study of 1.08 million women giving birth at least once between 1978 and 2011, we used Cox regression to estimate hazard ratios (HRs) comparing solid cancer rates for women with and without a history of HDP. In this cohort, 68, 236 women (6.3%) had ≥1 pregnancy complicated by HDP and 42, 236 women (3.9%) developed solid tumors during follow‐up. A history of HDP was not associated with a clinically meaningful reduction in the overall rate of solid cancer (HR 0.96, 95% confidence interval 0.92–1.00), regardless of HDP severity or time since HDP, nor was there a general tendency toward reduced solid cancer rates across organ sites. A history of HDP was only significantly associated with decreased rates of breast and lung cancers and with increased rates of endometrial and urinary tract cancers. Overall, our results do not support the hypothesis that women with a history of HDP have a reduced overall risk of solid cancer due to a persistent post‐HDP antiangiogenic state or an innate tendency toward antiangiogenesis. Observed associations with specific cancers may instead be due to other pregnancy‐related mechanisms or to residual/unmeasured confounding. Abstract : What's new? A central feature of preeclampsia, a hypertensive disorder of pregnancy (HDP), is antiangiogenesis, which is also key to restricting tumor growth. Hence, HDPs are suspected of being linked to a reduced risk of later solid cancers. Here, in a cohort of more than one million women, little evidence was found to support an association between HDP and reduced overall rates of solid cancer. No general tendency toward a reduction in site‐specific cancers was observed, refuting the idea that HDPs are linked to reduced solid cancer risk in general.